2022
DOI: 10.3390/microorganisms10020232
|View full text |Cite
|
Sign up to set email alerts
|

Condensate Formation by Metabolic Enzymes in Saccharomyces cerevisiae

Abstract: Condensate formation by a group of metabolic enzymes in the cell is an efficient way of regulating cell metabolism through the formation of “membrane-less organelles.” Because of the use of green fluorescent protein (GFP) for investigating protein localization, various enzymes were found to form condensates or filaments in living Saccharomyces cerevisiae, mammalian cells, and in other organisms, thereby regulating cell metabolism in the certain status of the cells. Among different environmental stresses, hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The growth defect of ADH1 -knockout cells was recovered by the introduction of plasmids for overexpressing ADH1 (S4 Fig in S1 File ), suggesting that the growth defect was due to the non-existence of ADH1 . Most enzymes of the glycolytic pathway that catalyze the metabolism of glucose to acetaldehyde and acetaldehyde to acetic acid are known to form condensates under hypoxia, while enzymes involved in glycerol and ethanol synthesis do not [ 9 ] (4B Fig). If the localization of Adh1p to intracellular META bodies or other condensates has no effect on cell metabolism, then the production of ethanol from glucose and the ratio of ethanol to acetic acid in culture media should be unchanged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth defect of ADH1 -knockout cells was recovered by the introduction of plasmids for overexpressing ADH1 (S4 Fig in S1 File ), suggesting that the growth defect was due to the non-existence of ADH1 . Most enzymes of the glycolytic pathway that catalyze the metabolism of glucose to acetaldehyde and acetaldehyde to acetic acid are known to form condensates under hypoxia, while enzymes involved in glycerol and ethanol synthesis do not [ 9 ] (4B Fig). If the localization of Adh1p to intracellular META bodies or other condensates has no effect on cell metabolism, then the production of ethanol from glucose and the ratio of ethanol to acetic acid in culture media should be unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Other enzymes, including purine biosynthetic enzymes, are known to form condensates termed the “Purinosome” in human-derived HeLa cells [ 7 , 8 ]. These multiple condensates of metabolic enzymes are collectively referred to as the “metabolic enzymes transiently assembling (META) body” [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the negatively charged l -lactate oxidase (LOX, p I = 6) can form enzyme assemblies in the presence of the positively charged poly- l -lysine (PLL), a polyelectrolyte that mimics IDRs at physiological pH, and trigger the activation of LOX 14 . Enzyme assemblies have been investigated as a mechanism of intracellular enzymatic activation 15 , 16 . The size of an enzyme assembly is important for enzyme activation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…b Unless mentioned otherwise, original references for the various enzymes can be found in comprehensive reviews by Park and Horton [15] and Montrose et al, [30] as well as more focused reviews. [6,17,18,[31][32][33][34][35][36][37] c See Reference [38]. d See References [39,40], and [41].…”
mentioning
confidence: 99%